Mistaken identity : two families, one survivor, unwavering hope - Van Ryn, Don (Howard Books, 2009)
When five Taylor University students and staff were killed in a tragic accident, one survivor---hospitalized and in a coma---was identified as Laura Van Ryn. Another young woman, Whitney Cerak, was buried. The discovery that the girls had been mistaken for each other changed their families forever. An amazing story of healing---and the bonds of faith! 288 pages, softcover from Howard.